2009
DOI: 10.1088/0022-3727/42/5/055108
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of strained nano-thin 3C–SiC/Si heterostructures

Abstract: The effects of strain on the conduction mechanism in heterostructures consisting of strained nano-thin 3C–SiC films on Si are reported. These films exhibit significantly different electrical behaviours than the bulk material. Strained nano-thin 3C–SiC films were grown on n-type Si substrates by gas source molecular beam epitaxy. Reflection high-energy electron diffraction patterns show that these films are about 3% strained relative to the SiC lattice constant. In order to investigate the electrical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…By taking the advantages of silicon-orientated mature MEMS processing technologies, 3C-SiC on the Si structure has opened a new platform to develop a wide range of better and low cost highly sensitive physical sensors for harsh environments. Although the best efforts have been made to grow high quality 3C-SiC film on Si-substrate, the grown 3C-SiC/Si heterojunction experiences crystal defects and film stress at the interfaces due to different thermal expansion coefficients and the lattice mismatch between 3C-SiC and Si [9], [10]. The crystal defects, mainly stacking faults, as well as film quality can be improved by carbonizing the active silicon surface before the deposition of 3C-SiC [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…By taking the advantages of silicon-orientated mature MEMS processing technologies, 3C-SiC on the Si structure has opened a new platform to develop a wide range of better and low cost highly sensitive physical sensors for harsh environments. Although the best efforts have been made to grow high quality 3C-SiC film on Si-substrate, the grown 3C-SiC/Si heterojunction experiences crystal defects and film stress at the interfaces due to different thermal expansion coefficients and the lattice mismatch between 3C-SiC and Si [9], [10]. The crystal defects, mainly stacking faults, as well as film quality can be improved by carbonizing the active silicon surface before the deposition of 3C-SiC [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…For completeness, we note that an additional potential reason for the degradation of the SiC/Si junction could be the reduced band gap arising from the residual tensile strain in the SiC epilayers. 9 That is, the band gap reduction results in a smaller valence band barrier and leads to increased hole current injection from the Si to the SiC. 9 To test the hypothesis of tensile strain-induced SiC band gap changes on the junction we simulated the SiC/Si system with the strained band gap and electron affinity values mentioned by Rahimi et al 9 and found that even a large concentration of those acceptor traps (up to ~10 20 cm -3 ) in the film does not appreciably contribute to the degradation of the heterojunction between the SiC film and the substrate.…”
Section: Discussion and Modelmentioning
confidence: 99%
“…2 Moreover, studies of strained heterostructures have shown that the substantial tensile strain generated from the lattice and thermal expansion coefficient mismatch between 3C-SiC and silicon may reduce the band gap of the SiC. 9 Nevertheless, a detailed explanation of the leakage/shorting phenomenon, and the impact of this challenge on the electrical properties of 3C-SiC layers are poorly documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been proposed that matrixSiC w stress transfer can explain observations of (tensile) whisker fracture instead of pullout: specifically, that the higher-modulus SiC whiskers unload the matrix and reduce stress around defects in the composite microstructure and result in an overall improvement in composite mechanical properties (Björk & Hermansson, 1989). The mechanical stress distribution within the SiC whiskers might also affect electrical response of composites because elastic strain was found to result in changes in electrical response of -SiC films and used to explain the observed back-to-back Schottky-barrier response (Rahimi et al, 2009). …”
Section: Effects Of Whisker Defect Structures and Interfaces On Variomentioning
confidence: 99%